IMPLEMENTASI EVALUASI BERBASIS WEB PADA PEMBELAJARAN ISMUBA DI SMA MUHAMMADIYAH 4 ANDONG - musa azzam al asy'ari; Zikroatul Nurul Uula; Rirmawati (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
This study verified the implementation of web-based evaluation on ISMUBA learning at SMA Muhammadiyah 4 Andong. The purpose of this study is to understand how to apply evaluation through the website, the benefits that will later be obtained when the evaluation process uses the website. The method used in this study is qualitative research method.  Types of field research, and phenomenological approaches. This research was carried out at SMA Muhammadiyah 4 Andong. Research data sources from Islamic religious education teachers, Muhammadiyahan education teachers, and website operators. The supporting data from the researcher also involved students, principals, and curriculum waka. Data collection techniques include interviews, observations, and document studies. This research is a descriptive analysis. The results of the implementation of web-based evaluation on ISMUBA, learning can motivate students to study harder and get increased learning outcomes, and students will prepare themselves to master the material to be tested, and the values obtained will be as expected. The success of this web-based implementation is due to the existence of tools used to access the website, cooperation between teachers and website operators in the process of uploading questions that will be evaluated, and also the understanding of students in accessing the website.